2019
DOI: 10.3390/app9235049
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors Analysis of Air Traffic Safety Based on HFACS-BN Model

Abstract: Air traffic control (ATC) performance is important to ensure flight safety and the sustainability of aviation growth. To better evaluate the performance of ATC, this paper introduces the HFACS-BN model (HFACS: Human factors analysis and classification system; BN: Bayesian network), which can be combined with the subjective information of relevant experts and the objective data of accident reports to obtain more accurate evaluation results. The human factors of ATC in this paper are derived from screening and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The HFACS model defines the failures at four levels: unsafe behaviours, preconditions for unsafe behaviours, unsafety supervision and organizational management (Figure 2). This model is not only suitable for pilot risk management systems, but also has a good application in air traffic control man-made risk control (Lyu et al, 2019). The risk factors are mutually associated and influenced and jointly constitute a set of pilot unsafe behavioural risks.…”
Section: Methodsmentioning
confidence: 99%
“…The HFACS model defines the failures at four levels: unsafe behaviours, preconditions for unsafe behaviours, unsafety supervision and organizational management (Figure 2). This model is not only suitable for pilot risk management systems, but also has a good application in air traffic control man-made risk control (Lyu et al, 2019). The risk factors are mutually associated and influenced and jointly constitute a set of pilot unsafe behavioural risks.…”
Section: Methodsmentioning
confidence: 99%
“…Each level corresponds to one layer of the Swiss Cheese Model. The advantage of HFACS is that it considers the organizational factors in the cause of accidents, which makes it an effective tool for the analysis of human factors in aviation accidents [ 34 ], and has been widely used in maritime [ 35 ], HCs transportation [ 36 ], mining [ 37 ], and other fields. However, the two approaches still consider that accidents are a result of a series of mutual causal events, although they do consider the complexity of the accident process and could reveal the relationship between potential cause and direct cause in the accidents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, there are many studies have used BN to identify causation factors of accidents or predict the safety status under certain conditions. For example, Xia et al [34] established BN model to predict the safety performance in the field of construction projects, while Tao et al [37] used BN-HFACs model to analyze the human factors of air traffic accidents. Although these studies applied in different scenarios or purposes, it can be concluded that BN could be used in this paper to analyze the causes of HCAs.…”
Section: Bn-hfacsmentioning
confidence: 99%